Cross-species metabolomic profiling reveals phosphocholine-mediated liver protection from cold and ischemia/reperfusion - Zhang, Lele; Chen, Liang; Jiang, Yong; Jin, Guanghui; Yang, Jinghong; Sun, Haobin; Liang, Jinliang; Lv, Guo; Yang, Qing; Yi, Shuhong; Chen, Guihua; Liu, Wei; et al. (American journal of transplantation, 2024)
Cold and ischemia/reperfusion (IR)-associated injuries are seemingly inevitable during liver transplantation and hepatectomy. Because Syrian hamsters demonstrate intrinsic tolerance to transplantation-like stimuli, cross-species comparative metabolomic analyses were conducted with hamster, rat, and donor liver samples to seek hepatic cold and IR-adaptive mechanisms. Lower hepatic phosphocholine contents were found in recipients with early graft-dysfunction and with virus-caused cirrhosis or high model for end-stage liver disease scores (≥30). Choline/phosphocholine deficiency in cultured human THLE-2 hepatocytes and animal models weakened hepatocellular cold tolerance and recovery of glutathione and ATP production, which was rescued by phosphocholine supplements. Among the biological processes impacted by choline/phosphocholine deficiency, 3 lipid-related metabolic processes were downregulated, whereas phosphocholine elevated the expression of genes in methylation processes. Consistently, in THLE-2, phosphocholine enhanced the overall RNA m6A methylation, among which the transcript stability of fatty acid desaturase 6 (FADS6) was improved. FADS6 functioned as a key phosphocholine effector in the production of polyunsaturated fatty acids, which may facilitate the hepatocellular recovery of energy and redox homeostasis. Thus, our study reveals the choline-phosphocholine metabolism and its downstream FADS6 functions in hepatic adaptation to cold and IR, which may inspire new strategies to monitor donor liver quality and improve recipient recovery from the liver transplantation process.